Revealing "Tut Wuri Handayani" - A Student-Centred Learning Approach- by Ki Hajar Dewantara from The Early 20th Century: A Literature Review - Mora Claramita (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2016)
Background: Student-centred learning is characterized by constructive, collaborative and contextual learning; derived from the constructivism theory. We studied the principle of “Tut Wuri Handayani” / TWH (to follow the learners to achieve their utmost potentials) which was initiated in 1922 by Dewantara, who was the first Ministry of Education, Republic of Indonesia.Method: A qualitative method with ‘content-analysis’ was used to study the articles written by Dewantara published in Indonesian newspapers between 1920-1960. We reflected the articles into current evidences of student-centred learning principles. Validations were done through three times focus group discussions (FGDs) by 30 students of a master’s of health professional education program and in-depth interview with two national experts in higher education.Results: In the period of early 20th century, Dewantara’s ideas had arrived at ‘contextual’ and ‘collaborative’ principles; the basis of current philosophy of student-centred learning. Dewantara’s exceptional initiatives were: (1) emphasizing equity between learners and teachers regardless the strong hierarchical social culture among Indonesian, (2) making the best use of cultural events and instruments as rigorous learning resources to enhance the sensory abilities and social sensitivity of the students towards community’s needs, (3) promoting observation-based learning to promote self-directed learning by helping the students to reflect on their mistakes, to be independent thinkers and to be responsible persons, to minimize gaps between attitudes and behaviours, and to provide role models and opportunities for students to actively participate in learning.Conclusion: “Tut Wuri Handayani” or ‘to follow the learners to achieve their utmost potentials’ revealed as a student-centred learning principle emphasizes life-long learning. Dewantara may be regarded as one of the world-wide leaders in education.